Evaluating the Efficacies of Carbapenem/β-Lactamase Inhibitors Against Carbapenem-Resistant Gram-Negative Bacteria in vitro and in vivo - El Hafi, Bassam; Rasheed, Sari S.; Abou Fayad, Antoine G.; Araj, George F.; Matar, Ghassan M. (Frontiers in Microbiology, 2019)
Background: Carbapenem-resistant Gram-negative bacteria are a major clinical concern as they cause virtually untreatable infections since carbapenems are among the last-resort antimicrobial agents. β-lactamases implicated in carbapenem resistance include KPC, NDM, and OXA-type carbapenemases. Antimicrobial combination therapy is the current treatment approach against carbapenem resistance in order to limit the excessive use of colistin; however, its advantages over monotherapy remain debatable. An alternative treatment strategy would be the use of carbapenem/β-lactamase inhibitor (βLI) combinations. In this study, we assessed the in vitro and in vivo phenotypic and molecular efficacies of three βLIs when combined with different carbapenems against carbapenem-resistant Gram-negative clinical isolates. The chosen βLIs were (1) avibactam, against OXA-type carbapenemases, (2) calcium-EDTA, against NDM-1, and (3) relebactam, against KPC-2. Methods: Six Acinetobacter baumannii clinical isolates were screened for blaOXA-23-like, blaOXA-24/40, blaOXA-51-like, blaOXA-58, and blaOXA-143-like, and eight Enterobacteriaceae clinical isolates were screened for blaOXA-48, blaNDM-1, and blaKPC-2. The minimal inhibitory concentrations of imipenem (IPM), ertapenem (ETP), and meropenem (MEM) with corresponding βLIs for each isolate were determined. The efficacy of the most suitable in vitro treatment option against each of blaOXA-48, blaNDM-1, and blaKPC-2 was assessed via survival studies in a BALB/c murine infection model. Finally, RT-qPCR was performed to assess the molecular response of the genes of resistance to the carbapenem/βLI combinations used under both in vitro and in vivo settings. Results: Combining MEM, IPM, and ETP with the corresponding βLIs restored the isolates’ susceptibilities to those antimicrobial agents in 66.7%, 57.1%, and 30.8% of the samples, respectively. Survival studies in mice revealed 100% survival rates when MEM was combined with either avibactam or relebactam against blaOXA-48 and blaKPC-2, respectively. RT-qPCR demonstrated the consistent overexpression of blaOXA-48 upon treatment, without hindering avibactam’s activity, while blaNDM-1 and blaKPC-2 experienced variable expression levels upon treatment under in vitro and in vivo settings despite their effective phenotypic results. Conclusion: New carbapenem/βLI combinations may be viable alternatives to antimicrobial combination therapy as they displayed high efficacy in vitro and in vivo. Meropenem/avibactam and meropenem/relebactam should be tested on larger sample sizes with different carbapenemases before progressing further in its preclinical development.